2018
DOI: 10.1101/260620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A proteolytic complex targets multiple cell wall hydrolases inPseudomonas aeruginosa

Abstract: 21Carboxy-terminal processing proteases (CTPs) occur in all domains of life. In bacteria, 22 they have been associated with virulence, but their roles are poorly understood. One is 23 the CtpA protease of Pseudomonas aeruginosa, which is required for type III secretion 24 system function, and for virulence. Here we show that CtpA works with a previously 25 uncharacterized binding partner to degrade four substrates. The accumulation of at 26

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…However, experiments with the Escherichia coli CtpA homolog Tsp showed that Tsp may preferentially bind substrates that possess a series of non‐polar residues or small, polar residues at the C‐terminus and that the nature of the final amino acid is most critical in substrate determination (Silber et al , ; Keiler et al , ; Keiler and Sauer, ). Although this characteristic is not required for targets of this family, as substrates that do not fit this scheme have been identified, the ECT does possesses an ultimate charged lysine, suggesting that the ECT may not serve as the CtpA substrate (Srivastava et al , ). Multiple observations suggest that a third, unidentified protease (P3) is responsible for removing C‐terminal residues to convert FhaB into a CtpA substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, experiments with the Escherichia coli CtpA homolog Tsp showed that Tsp may preferentially bind substrates that possess a series of non‐polar residues or small, polar residues at the C‐terminus and that the nature of the final amino acid is most critical in substrate determination (Silber et al , ; Keiler et al , ; Keiler and Sauer, ). Although this characteristic is not required for targets of this family, as substrates that do not fit this scheme have been identified, the ECT does possesses an ultimate charged lysine, suggesting that the ECT may not serve as the CtpA substrate (Srivastava et al , ). Multiple observations suggest that a third, unidentified protease (P3) is responsible for removing C‐terminal residues to convert FhaB into a CtpA substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Our data are consistent with direct interaction between CtpA and the prodomain. However, because it is likely that CtpA has multiple degradation targets, some of which may include homologs of identified target peptidoglycan hydrolases, it is possible that CtpA is necessary for prodomain degradation due to indirect effects, such as cleavage of another protein or changes in the peptidoglycan (Singh et al , ; Srivastava et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from E. coli and P. aeruginosa point towards proteolytic turnover (44, 45); however, in E. coli this mechanism of regulation appears to be more dominant during stationary phase remodeling and its role in P. aeruginosa is unclear. Notably, deleting EP-specific proteases only causes minor phenotypes under laboratory growth conditions and does not seem to affect cell elongation in exponential phase unless severe osmotic conditions are applied (44, 45). Here, we present data suggesting a conformational switch mechanism of activation for LysM/M23 EPs to effectively regulate cell wall remodeling during cellular expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The Gram-positive bacterium Bacillus subtilis (and likely other Gram-positive species as well) regulates EP activity via interactions with FtsEX and the PG synthesis elongation machinery (3537) and additionally encodes a post-translational negative regulator, IseA (YoeB) (38), which presumably serves to tone down EP activity during cell wall stress conditions (38, 39). Much less is known about EP regulation in Gram-negative bacteria, where EPs appear to be kept in check as part of multiprotein complexes (40, 41), at the transcriptional level (42, 43) or via proteolytic degradation (44, 45). Proteolytic turnover appears to be the major mode of regulation of growth-promoting EPs (44, 45); however, phenotypes associated with the accumulation of EPs have surprisingly mild phenotypes under normal growth conditions, suggesting an additional, unexplored layer of regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation